2022
DOI: 10.1111/jmwh.13394
|View full text |Cite
|
Sign up to set email alerts
|

Improved Self‐Assessed Collaboration Through Interprofessional Education: Midwifery Students and Obstetrics and Gynecology Residents Learning Together

Abstract: Introduction:Research suggests that interprofessional education, bringing learners together to learn about, with, and from each other, improves health professions education and can improve health outcomes. Little research has measured outcomes of interprofessional education between midwifery students and obstetrics and gynecology residents. The purpose of this study was to examine self-assessed interprofessional and collaborative competencies among midwifery students and obstetrics and gynecology residents.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Providing interprofessional education that incorporates understanding and respect for midwifery care can improve collaboration between midwives and physicians, as reported by the ACNM-American College of Obstetricians and Gynecologists Interprofessional Education demonstration project. 43 Practice leadership, including administrators and managers, can find creative approaches for midwives to have control over how they conduct their work, such as building their own schedules to accommodate work-life balance. A pathway for CNMs/CMs to align their personal and professional values with their work is to be granted full voting membership on their institution's medical staff, and on obstetrics and gynecology departmental committees that establish policies and procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing interprofessional education that incorporates understanding and respect for midwifery care can improve collaboration between midwives and physicians, as reported by the ACNM-American College of Obstetricians and Gynecologists Interprofessional Education demonstration project. 43 Practice leadership, including administrators and managers, can find creative approaches for midwives to have control over how they conduct their work, such as building their own schedules to accommodate work-life balance. A pathway for CNMs/CMs to align their personal and professional values with their work is to be granted full voting membership on their institution's medical staff, and on obstetrics and gynecology departmental committees that establish policies and procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings of this study, we have identified several concrete steps that educators, administrators, policymakers, and midwives can take to address burnout by improving the practice environment. Providing interprofessional education that incorporates understanding and respect for midwifery care can improve collaboration between midwives and physicians, as reported by the ACNM-American College of Obstetricians and Gynecologists Interprofessional Education demonstration project 43. Practice leadership, including administrators and managers, can find creative approaches for midwives to have control over how they conduct their work, such as building their own schedules to accommodate work-life balance.…”
Section: Discussionmentioning
confidence: 99%
“…Often conducted or tested in higher-education environments, such learning activities worked to further healthcare organizational outcomes or other performance indicators [22,26,27,37]. Additionally, several team-based learning initiatives also infused interprofessional learning and collaboration [37,40]. Often driven by difficult clinical situations, patient diagnoses, or other environmental factors, the use of team-based learning has demonstrated the ability to improve organizational metrics and support the organizational leadership's initiatives [42,47].…”
Section: Organizational Leadership Team-based Learning/collaborationmentioning
confidence: 99%
“…The grant project, “ ACNM-ACOG Maternity Care Education and Practice Redesign ,” was further intended to address provider shortages in maternity care, align accreditation standards of the 2 professions related to interprofessional education (IPE), and find solutions to IPE challenges 1. The grant's goals included developing and implementing a model curriculum of IPE for graduate midwifery students and obstetrics and gynecology (OB-GYN) residents at multiple diverse demonstration sites 1,2. This article describes one demonstration site's solution to IPE challenges through distance synchronous interprofessional simulations.…”
mentioning
confidence: 99%
“…1 The grant's goals included developing and implementing a model curriculum of IPE for graduate midwifery students and obstetrics and gynecology (OB-GYN) residents at multiple diverse demonstration sites. 1,2 This article describes one demonstration site's solution to IPE challenges through distance synchronous interprofessional simulations.…”
mentioning
confidence: 99%